Fabrication of mechanically resistant ZnO-based superhydrophobic material for enhanced concrete applications - Mergen Zhazitov; Muhammad Abdullah; Nazerke Kydyrbay; Enoch Adotey; Zhexenbek Toktarbay; Tolagay Duisebayev; Yerbolat Tezekbay; Nurxat Nuraje; Olzat Toktarbaiuly (Case Studies in Construction Materials)
Concrete surfaces are particularly vulnerable to environmental degradation caused by factors such as moisture, freeze-thaw cycles, and mechanical abrasion, which lead to cracking, reduced structural integrity, and frequent maintenance. To address this problem, we have developed superhydrophobic coating specifically designed to provide enhanced durability and water resistance to concrete surfaces. The coating formulation, based on zinc oxide (ZnO), stearic acid (STA), and a silane compound acting as a hardening agent, successfully achieved the desired properties. Testing showed that the optimized formulation demonstrated excellent water repellency, with a contact angle of 154 degrees, placing it well within the superhydrophobic range. Characterizations such as using Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), goniometry, and X-ray diffraction (XRD) were conducted to assess the chemical composition, surface morphology, and physical properties of the coating. The results confirmed that the optimized ZnO-STA-silane coating maintained its superhydrophobic properties even after repeated mechanical abrasion and exposure to environmental stressors such as UV radiation, temperature fluctuations, and moisture.